REBECCA AS A SOCIAL CRIMINAL IN THACKERAY’S VANITY FAIR - Niğmet METİNOĞLU (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2022)
The scheming and calculating anti-heroine, Rebecca Crawley, Rebecca Sharp with her former name, is one of the female protagonists portrayed by William Makepeace Thackeray in his novel, Vanity Fair (1848). As an amoral woman of disadvantageous origins, she has the desire to become a respectful and influential person. However, on the way to achieving her ambition, her love of money and desire for a higher social status lead her to commit several crimes such as disregarding her son, cheating on her husband, and manipulating people. The views about Becky differ. It is still disputed if she is a person of guilt or an innocent and sympathetic individual who does what she must to gain higher status and affluence in a society in which a woman does not have many choices or possibilities to have what she desires. If she does not act the way she does, she will not be able to get by, or worse, she will have to do jobs degrading for women under the social conditions of the first half of the nineteenth century during the Regency period. This study aims to briefly dwell on the titles and the subtitles of Vanity Fair and treat Becky as a person who comes from humble origins and struggles to climb the social ladder by resorting to any kind of misdeed to help her way up, which would normally make her a social criminal, yet it is disputed because she is found relatable due to the conditions of the time.